Role of Mobile Health Team in Implementation of Rashtriya Bal Swasthya Karyakram: A Study of Shimla District of Himachal Pradesh - Kumar, Rajeev (International Journal of Applied and Scientific Research, 2024)
The Rashtriya Bal Swasthya Karyakram, launched by the Government of India, endeavors to ensure holistic healthcare for children up to the age of 18 years. Given the diverse and often challenging geographical terrain of Shimla District, the deployment of mobile health teams becomes imperative in reaching remote and underserved areas. This research paper investigates the pivotal role played by mobile health teams in the successful implementation of the Rashtriya Bal Swasthya Karyakram (a National Child Health Program) in the context of Shimla District of Himachal Pradesh. The overarching objective of this study is to provide a nuanced understanding of how mobile health teams contribute to the success of this vital public health initiative, specifically tailored to address the health needs of children and adolescents. The research employs a qualitative approach, utilizing interviews, surveys, and observational data to assess the role of these teams on the children health outcomes in the region. The study places particular emphasis on preventive and promotive healthcare measures implemented by these mobile health teams. By focusing on early detection of health issues and timely interventions, the research aims to assess the overall improvement in health outcomes among the targeted demographic. The findings of this research are expected to contribute significantly to the existing body of knowledge on public health interventions, specifically within the realm of child health. The nuanced understanding of the operational dynamics of mobile health teams in Shimla District can serve as a blueprint for refining similar initiatives in diverse geographic and demographic settings. Moreover, the insights garnered from this study may inform policy decisions aimed at enhancing the efficiency and impact of mobile health teams in the broader landscape of public health programs.